Growth curves and nutritional requirements for maintenance of asymptotic weight of Nellore cattle - de Arruda, Rosana; Souza, Júlio; Jardim, Rodrigo José; Ferraz Filho, Paulo; Silva, Luiz Otávio (Revista Ciência Agronômica, 2018)
The objective of this study was to evaluate the growth curve of Nellore cattle raised in the Pantanal, Mato Grosso do Sul, in different groups of size (weight), sex, and birth season, as well as to estimate the nutritional requirements for maintenance of the asymptotic weigh. The nonlinear models were adjusted using the Gauss-Newton method, with information on weight and age of animals within each (total, upper, and middle) group. The asymptotic weight was influenced by sex (P<0.05) in all groups. Regarding maturity rates, females in the total herd and upper group were more precocious than males, whereas males and females in the middle group were similar. Animals born in the dry season of the year showed a greater asymptotic weight in the total herd and upper group, and significant difference was not observed only in the middle group. Regarding asymptotic weight for the growth curve of the total herd (318.5 ± 0.92 kg), the upper group (384.4 ± 1.74 kg) requires 15.1% more nutrients for their daily maintenance. The nutritional requirements for daily maintenance in the middle group (294.5 ± 1.00 kg) is 5.7% lower than in the total herd. The animals kept in the same herd (in the Pantanal conditions) showed different growth curves, as a function of the birth season and sex, indicating variations in growth and different energy requirements for their maintenance.